ST-Segment Elevation Myocardial Infarction and Right Atrial Myxoma - Vondran, Maximilian; Ghazy, Tamer; Andrási, Terézia Bogdana; Rastan, Ardawan Julian (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Cardiac myxoma is the most common primary cardiac tumor. Although benign, it can cause life-threatening complications due to embolization.Case Presentation We describe an ST-elevation myocardial infarction (STEMI) involving a giant right atrial myxoma and persisting foramen ovale (PFO) in a 64-year-old male patient and report on emergency percutaneous interventional therapy and subsequent cardiac surgery to remove the right atrial myxoma.Conclusion A right atrial myxoma, combined with a PFO, can cause a STEMI. Therefore, every acute coronary syndrome patient should undergo ultrafast exploratory emergency echocardiography to protect the physician from unpleasant surprises.
Keywords: myocardial infarction; myxoma; cardiac catheterization/interventionpercutaneous coronary intervention; cardiovascular surgery; echocardiography; tumor